Creativity and successful product concept selection for innovation. Issue 1 (2nd January 2021) - Guenther, Agnes; Eisenbart, B.; Dong, A.
ABSTRACT: Selecting novel product concepts for further development into successful innovations entails decision making under conditions of high uncertainty. The literature discusses several influencing factors for making accurate decisions in such situations, such as domain expertise to evaluate technical feasibility and market potential. Recent scholarship increasingly highlights the decision makers' personal creative capabilities to have an important influence in dealing with uncertain options. This article examines an individual's creativity and its relation to the individual's propensity to select novel product concepts and to choose product concepts correctly for further development. We present an experimental study showing that an individual's level of creativity increases the likelihood of accepting novel product concepts without negatively affecting decision accuracy. Domain expertise operationalized as familiarity with the intended, central use case or technology in the product concept neither influences the likelihood of accepting new product concepts nor decision accuracy. These findings have strong implications for companies in relation to managing individuals selecting product concepts for further development in early stages of the innovation process.